2009
DOI: 10.1021/bm801136m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Partly Fluorinated Block Copolymers as MRI Imaging Agents

Abstract: A series of well-defined diblock copolymers of acrylic acid with partially fluorinated acrylate and methacrylate monomers were synthesized using ATRP as potential 19F MRI imaging agents. The diblock copolymers could undergo spontaneous self-assembly in mixed and aqueous solvents to form stable micelles with a diameter from approximately 20-45 nm, having a fluorine-rich core that provides a strong signal for MRI examinations. The observed MRI image intensities were related to the NMR longitudinal and transverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
125
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 20 publications
6
125
0
Order By: Relevance
“…Alternatively, 19 F MRI holds several unique advantages such as low endogenous background signals, high signal-to-noise ratio (SNR), 100% natural isotopic abundance, relatively high sensitivity (83% of proton) and broad range of chemical shifts. [26][27][28][29] To date, some exogenous contrast agents such as molecular probes with a number of equivalent fluorine atoms, [27,[30][31][32][33][34][35] polymeric tracers containing high numbers of fluorine atoms, [28,[36][37][38][39][40][41][42] and fluorinated metallic nanoparticles [43][44][45][46] have been developed and employed for 19 F MRI. Despite great successes, it is highly desirable and still challenging to develop suitable 19 F MRI contrast agents with satisfied performance as well as multi-modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, 19 F MRI holds several unique advantages such as low endogenous background signals, high signal-to-noise ratio (SNR), 100% natural isotopic abundance, relatively high sensitivity (83% of proton) and broad range of chemical shifts. [26][27][28][29] To date, some exogenous contrast agents such as molecular probes with a number of equivalent fluorine atoms, [27,[30][31][32][33][34][35] polymeric tracers containing high numbers of fluorine atoms, [28,[36][37][38][39][40][41][42] and fluorinated metallic nanoparticles [43][44][45][46] have been developed and employed for 19 F MRI. Despite great successes, it is highly desirable and still challenging to develop suitable 19 F MRI contrast agents with satisfied performance as well as multi-modalities.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,4,5,[21][22][23] The rarity of physiologic fluorine can be exploited to generate highly selective, 19 F images that can be superimposed over complimentary 1 H images, thus providing an anatomical context for the fluorinated contrast agent. [9,23,24] Research in this area has focused on the synthesis of fluorinated nanoparticles using a variety of different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have created novel fluorinated amphiphilic block copolymers that form micelles in aqueous solution. [1,4,5,27] Typically, a living free radical polymerization method is employed to synthesize such amphiphilic block copolymers. [1,5,27] This polymer self assembles in water and the resulting suspension is used as the contrast agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of large quantities of these moieties in an amphiphilic material, dispersed in aqueous media, can require long image acquisition times (hours). 257,258 It has been shown that the T 2 relaxation time of these fluorinated species is a good indicator of imaging performance, and that longer T 2 times were achieved by maintaining high mobility and flexibility of fluorinated groups. [259][260][261] By copolymerising fluorinated monomers into a hyperbranched polymer with a water soluble monomer (dimethylaminomethyl methacrylate), the association of the fluorinated groups was frustrated and imaging times decreased dramatically (< 10 minutes).…”
Section: -256mentioning
confidence: 99%